2022
DOI: 10.3389/fped.2022.937246
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of pediatric keratoconus by different age and gender groups

Abstract: PurposeTo evaluate the distribution of pediatric keratoconus patients and the disease severity based on different age and gender groups in China.Materials and methodsA total of 446 keratoconus eyes in 266 pediatric patients from January 2019 to January 2022 were included in the cross-sectional study. The clinical findings and severity of keratoconus were recorded and Kruskal–Wallis test, chi-squared test, and Cochran-Mantel-Haenszel (CMH) test were used to compare the parameters between different gender and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(87 reference statements)
0
3
1
Order By: Relevance
“…Some studies have suggested that KCN is a male-predominant disease. 28,30 However, in this study, black men were less likely to present with KCN than non-black men. This could be explained by the theory that black men have less trust in the medical system than other populations, such as black women or white men, 31 making them less likely to present for an evaluation.…”
contrasting
confidence: 57%
“…Some studies have suggested that KCN is a male-predominant disease. 28,30 However, in this study, black men were less likely to present with KCN than non-black men. This could be explained by the theory that black men have less trust in the medical system than other populations, such as black women or white men, 31 making them less likely to present for an evaluation.…”
contrasting
confidence: 57%
“…The limited sample of pediatric SKC eyes would result in a lack of research evidence of the diagnosis criteria of pediatric SKC eyes. In addition, our previous study reported that pediatric unilateral patients account for 7.82% of all KC patients (86/1,100), ( Yang et al, 2022 ), which might be related to the fact that the minimum age approved for corneal refractive surgery is 18 years and corneal tomography and biomechanics are not commonly examined in children. ( Ortega-Usobiaga et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This case-control study enrolled 52 control eyes, 52 SKC eyes, and 52 KC eyes of individuals aged <18 years between January 2019 and January 2022 in the Henan Eye Hospital. KC was included as per previous criteria: ( Yang et al, 2022 ): an asymmetric bowtie pattern with or without skewed axes, a Belin Ambrosio enhanced ectasia total deviation index (BAD-D) value > 2.6 by corneal topography, and a positive slit-lamp sign (localized stromal thinning, Vogt’s striae, Fleischer’s ring, conical protrusion, or anterior stromal scar). The SKC eye in the current study was defined as no clear evidence of KC in one eye, with the contralateral eye meeting the above KC diagnostic criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects of the case‒control study were patients from the Henan Eye Hospital during 2019–2022. Details of the design of the case‒control study have been described elsewhere [ 14 , 18 , 19 ]. Briefly, in this study, the participants were recruited based on age (3 years) and sex.…”
Section: Methodsmentioning
confidence: 99%